Menopausal Implications of Polycystic Ovarian Syndrome - Kudesia, Rashmi; Neal-Perry, Genevieve S. (Seminars in Reproductive Medicine, 2014)
Polycystic ovary syndrome (PCOS) is a common endocrinopathy affecting up to 8 to 10% of reproductive-aged women. Although the medical and metabolic consequences of PCOS are well-described in young reproductive-aged women, its impact on female reproductive senescence and the menopausal transition is poorly understood. This review summarizes current knowledge regarding the effect of PCOS is menopausal and perimenopausal women. We also highlight areas that are ripe for clinical research.
Keywords: menopause; PCOS; hormone therapy